(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is the most reported pathogen in hand infections at medical centers throughout the world. Antibiotic sensitivity trends are not well known. The purposes of this study were to examine and determine the drug resistance trends for MRSA infections of the hand and to provide recommendations for empiric antibiotic treatment based on sensitivity profiles Objectives: A 05-year longitudinal, retrospective review was performed on all culture-positive hand infections encountered in HTO from 2019 to 2023. The proportions of all organisms were calculated for each year and collectively. MRSA infections were additionally subanalyzed for antibiotic sensitivity Results: A total of 369 culture-positive hand infections were identified. Overall, MRSA grew on culture in 38% of cases. A trend toward decreasing annual MRSA incidence was noted over the 05-year study period. There was a steady increase in polymicrobial infections during the same time. Resistance to clindamycin increased steadily during the 05-year study, starting at 53.85% in 2021 but growing to 78.26% by 2023. Similarly, levofloxacin resistance consistently increased throughout the study, reaching its peak at 60.71% in 2019 ; however, decreasing at 29.17% in 2023 Conclusions: The annual incidence of MRSA in hand infections remains the most common pathogen. There has been an alternative increase in the number of polymicrobial infections. MRSA resistance to clindamycin and levofloxacin consistently increased during the study period. Empiric antibiotic therapy for hand infections should not only avoid penicillin and other beta-lactams but should also consider avoiding clindamycin and levofloxacin for empiric treatment.